Assessment of coupled hydrologic and biogeochemical Hg cycles in a temperate forestry watershed using SWAT-Hg. (April 2020) - Jeong, Jaehak; Yang, Jisook; Han, Seunghee; Seo, Yong-Seok; Hong, Yongseok
Abstract: Terrestrial and aquatic mercury biogeochemical processes are integrated into the Soil and Water Assessment Tool (SWAT) to simulate the watershed scale Hg behaviors. The SWAT-Hg was successfully calibrated and validated with the data obtained from the Jang-Sung Dam (JSD) watershed. The largest Hg storage in the watershed was found in soil (93%), however, soil erosion was not the largest Hg source for the JSD reservoir due to the well-established forests. The model suggests the baseflow is the most dominant Hg loading to the waterbody, which accounts for 80.0% of the THg yields on the annual basis. The model simulation was projected to the year 2040 and showed that the Hg levels in various compartments of watershed have not reached to steady state, hence the Hg levels changed slowly over the decades even in status quo atmospheric Hg deposition. Graphical abstract: Image 1 Highlights: Watershed scale Hg biogeochemical processes are integrated into the SWAT. The largest Hg storage in the watershed was found in soil. The baseflow is the most dominant Hg loading to a waterbody in forestry watershed. The model showed that the Hg levels in water changed slowly over the decades.